Relationship of nutritional status with diarrhea among children in Sumenep Regency - Irma Nurma Linda; Menik Sri Daryanti (Universitas 'Aisyiyah Yogyakarta, 2022)
Nutritional problems can cause other diseases such as diarrhea. Diarrhea is a state of abnormal stool discharge. This disease attacks all age groups including childrenunder 5 years of age. The objective of the study is to determine the relationship between nutritional status and the incidence of diarrhea in toddlers. This study used a cross sectional design with an observational. Sampling used total sampling technique with 182 toddlers. The data taken was primary data by interviewing mothers of toddlers. The result of the study using chi square statistical test (α=0,05) wsa found p value 0,001 that mean there was a significant relationship between nutritional status with diarrhea.